Myocardial perfusion after marathon running - Kallokoski, K. K.; Laaksonen, M. S.; Luotolahti, M.; Laine, H.; Takala, T. O.; Nuutila, P.; Knuuti, J. (Scandinavian Journal of Medicine & Science in Sports, 2004)
We investigated the effects of acute prolonged exercise (marathon running) on cardiac function and myocardial perfusion. Cardiac dimensions and function were measured in seven endurance-trained men using echocardiography before and repeatedly after marathon (42.2 km) running (at 10 min, 150 min, and 20 h). Myocardial perfusion and perfusion resistance were measured using positron emission tomography and 15O-H2O before and 85-115 min after running. Echocardiographic indices showed only mild and clinically non-significant changes in cardiac function after running. Rate-pressure-corrected basal myocardial perfusion (0.89±0.13 vs. 1.20±0.32 mL min-1 g-1, P=0.04) was increased after running. Also, adenosine-stimulated perfusion tended to be higher (3.67±0.81 vs. 4.47±0.52 mL min-1 g-1, P=0.12) and perfusion resistance during adenosine stimulation was significantly lower after running (26±6 vs. 18±3 mmHg min g mL-1, P=0.03). Plasma free fatty acid (FFA) concentration was significantly increased after running. These results show that marathon running does not cause marked changes in cardiac function in healthy men. Basal perfusion was increased after exercise, probably reflecting changes in fuel preferences to increased use of FFAs. Strenuous exercise also seems to enhance coronary reactivity, which could thereby serve as a protective mechanism to vascular events after exercise.